An Investigation of the Cultural Significance and Symbolism of Limas House Architecture in the Lives of the South Sumatran People - Sulistiawati, Erika (Enigma Institute, 2023)
Limas houses, known for their unique features like tiered roofs, serve as more than mere architectural constructions. They embody a cultural emblem that signifies equilibrium, safeguarding, good fortune, affluence, and robust communal bonds in the everyday existence of the inhabitants of South Sumatra. The tiered roof symbolizes equilibrium and concord, representing the conviction in a harmonious interconnection among humanity, nature, and the spiritual realm. A Limas house is believed to provide protection against malevolent spirits and negative energy, fostering a sense of security and tranquility. Moreover, the Limas house is frequently associated with a sign of auspiciousness and affluence, with the expectation that its existence will bestow blessings upon the household and its inhabitants. Limas houses serve as venues for traditional ceremonies, including weddings, births, and funerals. It serves as a prominent emblem of social interaction and enhances the bonds among individuals within a community. Limas homeowners are renowned for their magnanimity, willingly extending hospitality to guests and individuals in need.